Preliminary Study: Opportunities for Utilizing Local Wisdom in Physics Learning to Enhance Scientific Argumentation - Nur Afni Agustinaningrum; Diah Krisdiyanti; Suliyanah Suliyanah; Nina Fajriyah Citra (Mitra Edukasi dan Publikasi, 2025)
The era of globalization requires every individual to possess scientific argumentation skills. However, in reality, many people have yet to apply approaches that emphasize scientific argumentation. One effective way to foster scientific argumentation skills is through learning that incorporates local wisdom. Therefore, this study was conducted with the aim of obtaining an overview of whether students show a tendency toward local wisdom-based learning in physics as a means to enhance scientific argumentation skills. This research employs a quantitative descriptive method. The data collection techniques used include questionnaires supported by interviews. The instruments utilized are a questionnaire sheet and an interview sheet. The data obtained were analyzed quantitatively and descriptively using a Likert scale. The results indicate that students perceive the need for learning that is not only focused on theoretical content but also integrates local values as a medium for developing critical thinking and scientific argumentation skills. Hence, it can be concluded that students recognize the importance of local wisdom-based learning as a potential approach to support the development of scientific argumentation skills. Local wisdom provides relevant context in physics learning. Thus, local wisdom-based learning is considered a meaningful approach to strengthen scientific argumentation skills and conceptual understanding in physics.